Prospective Open‐label Trial of Early Concomitant Vasopressin and Norepinephrine Therapy versus Initial Norepinephrine Monotherapy in Septic Shock. Issue 5 (30th April 2018) - Hammond, Drayton A.; Ficek, Oktawia A.; Painter, Jacob T.; McCain, Kelsey; Cullen, Julia; Brotherton, Amy L.; Kakkera, Krishna; Chopra, Divyan; Meena, Nikhil
Abstract : Purpose: Delays in achieving target mean arterial pressure (MAP) are associated with increased morbidity and mortality in patients with septic shock. This trial was conducted to test the hypothesis that early concomitant treatment with vasopressin and norepinephrine reduces the time to achieve and maintain target MAP compared with initial norepinephrine monotherapy. Methods: A single‐center prospective open‐label trial was conducted in patients with septic shock between November 2015 and June 2016 at a medical intensive care unit in an academic medical center. Initial norepinephrine monotherapy was initiated between November 2015 and February 2016. Between March and June 2016, vasopressin was initiated within 4 hours of norepinephrine. The primary outcome was time to achieving and maintaining MAP of 65 mm Hg for at least 4 hours that was compared between groups using the Student t test and examined using the Kaplan‐Meier curve (Clinical Trials registration: NCT02454348). Results: Eighty‐two patients were included (41 in each group). Patients treated with early concomitant vasopressin and norepinephrine more frequently had a positive culture (59% vs 37%, p=0.05) and grew nonlactose fermenting gram‐negative bacilli (34% vs 10%, p=0.01) compared with patients treated with norepinephrine monotherapy, respectively. The median time to achieve and maintain MAP occurred faster in the early concomitant vasopressin and norepinephrine group, at 5.7 hours (interquartile range [IQR] 1.7–10.3 hrs), compared with 7.6 hours (IQR 3.6–16.7 hrs, p=0.058) in the norepinephrine group. Durations of therapy for norepinephrine or vasopressin, amount of norepinephrine received in the first 24 hours, norepinephrine dosage when MAP was achieved and maintained, maximum norepinephrine dosage, and mortality were similar between groups. Conclusion: Patients treated with early concomitant vasopressin and norepinephrine achieved and maintained MAP of 65 mm Hg faster than those receiving initial norepinephrine monotherapy, suggesting that overcoming vasopressin deficiency sooner may reduce the time patients spend in the early phase of septic shock.